Estrategias de afrontamiento para controlar ansiedad en población indígena joven. Comunidad Ilincho. Loja, 2021 - Chalán Lozano, Nataly Yesenia (2022)
The present research analyzed the Anxiety and coping strategies in young people of the community of Ilincho, Saraguro canton, province of Loja, in the year 2021. It was done with a population of 200 indigenous youth between 18 and 29 years old. This study was field research, non-experimental cross-sectional design, with a quantitative approach and descriptive level. Instruments used were: the Beck Anxiety Inventory (BAI) of 21 items designed to evaluate the severity of anxious symptomatology and also the Coping Strategies Scale (CSI) consisting of 28 items that determine the coping strategies used by the young people; which were systematized and sent through a link so that they could be answered, obtaining the following results: the anxiety level presented by the young people was mild with 65%, and as for the coping strategies, evasion and conformism was the predominant strategy with a percentage of 54%. Based on the results, it can be seen that there is a slight level of anxiety on the part of the young people themselves who, in turn, are unaware of healthy strategies and, therefore, come to use avoidance and conformity as coping strategies. For that reason, an intervención protocol was developed in order to educate about diferente coping enchiques that will reduce anxiety levels and therefore contribute to the improvement of mental health of young people.